2016
DOI: 10.20450/mjcce.2016.944
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and bioactive compounds of stalk from hot fruits of Capsicum annuum L.

Abstract: In stalk of red hot pepper (Capsicum annuum L.) with 0.25 mm, 0.5 mm and 1.0 mm particle sizes, the quantities of nutritive and volatile compounds, bioactive capsaicin and carotenoids were determined. Furthermore, the stalk was characterized using TGA, DSC and FTIR spectroscopy. The influence of the particle size on the content of proteins, ash and cellulose is insignificant. Compared to 0.5 and 1.0 mm, stalk with 0.25 mm particle size was darker with a deeper yellow-brown color, and richer in microelements. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In this study, fruits were harvested 208 days after sowing, in the fully mature stage (orange color). Afterwards, they were washed with a 3% sodium hypochlorite solution and dried in a cool and ventilated place [33]. After drying, the effect of ZnSO 4 and ZnO NPs on fruit quality was evaluated on 10 uniform fruits without defects (physical or pathological damage) selected from each of the five replications per treatment [34].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, fruits were harvested 208 days after sowing, in the fully mature stage (orange color). Afterwards, they were washed with a 3% sodium hypochlorite solution and dried in a cool and ventilated place [33]. After drying, the effect of ZnSO 4 and ZnO NPs on fruit quality was evaluated on 10 uniform fruits without defects (physical or pathological damage) selected from each of the five replications per treatment [34].…”
Section: Methodsmentioning
confidence: 99%
“…have been studied because of the importance they have in many plants as pollinator attractors and their influence in odor and flavor, which are key features of any edible vegetable [59,60]. Some of the most valuable are hexyl isopentanoate, hexyl isobutanoate, and β-ionone [61]. Extracts of C. annuum have also showed high levels of 4-methoxyphenol, ethylhexadecanoate, hexanal or isopulegol [62].…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…Furthermore, processing waste by-products of fruits and vegetables are being researched as a viable source of phytochemicals that would be affordable and reduce economic and ecological impacts of wasted by-products or taking produce out of the food market [67,68]. Thus, fractions that are not employed in nourishment such as the placenta, seeds or leaves of many species can prove to be a valuable resource instead of end as waste or fertilizer, which is the most common use for vegetable non-edible parts [61].…”
Section: Bioactivities Of the Raw Materialsmentioning
confidence: 99%
“…1,2 The dried fruits of red chili pepper contain 18% proteins, ~3% fats, 26% cellulose, 6% reductive sugars, 9 mg/kg Cu, 14 mg/kg Zn, ~80 mg/kg Mn, and around 160 mg/kg Fe. 3,4 Beta-Ionone was found as the main volatile compound that is responsible for the chili peppers' odor. 5 Freire et al 6 found the following organic compounds in different chili pepper extracts: flavones, flavonols, xanthones (fraction in hexane or ethyl acetate of the ethanol extract), and free steroids (fraction in ethyl acetate or methanol of the ethanol extract), while saponins were found just in the fraction in methanol of the ethanol extract.…”
Section: Introductionmentioning
confidence: 99%